Persepsi dan Tantangan Pengembangan Bisnis Padi Organik Berbasis Wakaf Produktif: Studi Kasus Majelis Wakaf dan Kehartabendaan PDM Kab. Tasikmalaya - Jafril Khalil; Amrizal; Fahmi Faishal Malik (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the perceptions and challenges faced by Majelis Wakaf dan Kehartabendaan (MWK) of Pimpinan Daerah Muhammadiyah (PDM) in Tasikmalaya Regency regarding the management of waqf assets for organic rice farming businesses. The research method used is qualitative descriptive with purposive sampling technique. Data collection is done through observation, interviews, and documentation. The data analysis technique applied is thematic analysis. The results of the study show that: 1) There is a positive perception regarding the use of productive waqf for organic rice farming businesses. However, the dynamic external environment introduces uncertainty that affects development strategies. 2) The challenges involve strengthening member participation, improving agricultural human resources, institutional reinforcement, and expanding marketing.